2013
DOI: 10.1103/physrevd.87.104037
|View full text |Cite
|
Sign up to set email alerts
|

Bouncing loop quantum cosmology fromF(T)gravity

Abstract: The big bang singularity could be understood as a breakdown of Einstein's General Relativity at very high energies. Adopting this viewpoint, other theories, that implement Einstein Cosmology at high energies, might solve the problem of the primeval singularity. One of them is Loop Quantum Cosmology (LQC) with a small cosmological constant that models a universe moving along an ellipse, which prevents singularities like the big bang or the big rip, in the phase space (H, ρ), where H is the Hubble parameter and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
101
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 121 publications
(103 citation statements)
references
References 86 publications
2
101
0
Order By: Relevance
“…And Ref. [18] showed that super-inflation can support enough e-folding number while the Universe contains matter and a small cosmology constant Λ. Also, If one considers the Universe contains a scalar field or multiple scalar field with exponential potentials, the super-inflation is also possible to yield enough e-folding number [16].…”
Section: Horizon Problemmentioning
confidence: 99%
See 4 more Smart Citations
“…And Ref. [18] showed that super-inflation can support enough e-folding number while the Universe contains matter and a small cosmology constant Λ. Also, If one considers the Universe contains a scalar field or multiple scalar field with exponential potentials, the super-inflation is also possible to yield enough e-folding number [16].…”
Section: Horizon Problemmentioning
confidence: 99%
“…To solve the horizon problem, we require that aH grows sufficiently during an early stage of the Universe's evolution. In fact, we needN ≡ ln a(t f )H(t f ) a(ti)H(ti) ∼ 60 at least [18]. In the standard inflation theory, the Hubble parameter H is nearly a constant, so the e-folding number is depending on the change of the scale factor, i.e.,N = N ≡ ln a f ai .…”
Section: Horizon Problemmentioning
confidence: 99%
See 3 more Smart Citations